2015
DOI: 10.1111/ced.12560
|View full text |Cite
|
Sign up to set email alerts
|

Granulysin expression increases with increasing clinical severity of psoriasis

Abstract: These findings suggest a role for granulysin in psoriasis pathogenesis, and may explain the triggering effect of skin infection in psoriasis. If the pathogenic role of granulysin is substantiated by further studies, granulysin may be a potential target for immunomodulatory therapy for psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…GNLY + T cells are mainly found in the papillary dermis of psoriatic plaques and their number increases with increasing clinical severity of disease (9,10). Herein, for the first time, we demonstrated that CD8 + T lympho cytes and NK cells expressing GNLY molecule were several times more frequent in psoriasis skin, especially in epidermis compared to nonlesional and healthy skin.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…GNLY + T cells are mainly found in the papillary dermis of psoriatic plaques and their number increases with increasing clinical severity of disease (9,10). Herein, for the first time, we demonstrated that CD8 + T lympho cytes and NK cells expressing GNLY molecule were several times more frequent in psoriasis skin, especially in epidermis compared to nonlesional and healthy skin.…”
Section: Discussionmentioning
confidence: 65%
“…The presence of GNLY was only recently detected in psoriatic lesions. However, its specific involvement and role in psoriasis pathogenesis is still unclear (9,10).…”
Section: Significancementioning
confidence: 99%
“…5 , 6 It is known that antimicrobial peptides (AMPs), which provide high resistance to skin infection, show increased synthesis in psoriatic lesions. 7 AMP production in the skin is the primary mechanism that protects skin against infections, and AMP levels are increased as a result of microbial infections. 8 Granulysin is a member of the AMP family of cytolytic and proinflammatory peptides.…”
Section: Introductionmentioning
confidence: 99%
“…A study including patients with psoriasis revealed that GNLY expressions in patients were found to be significantly higher in comparison to healthy control group and also, the higher their GNLY levels were related to the duration of disease. According to these results, it was believed that GNLY could have an important role in the pathogenesis of psoriasis 21 .…”
Section: Discussionmentioning
confidence: 96%